Preliminary Screening of Proteinaceous and Glycerol-Related Compounds in Commercial Cigarette Filters: Implications For Halal Critical Point Assessment - Sumarlin, La Ode; Andrianto, Dimas; Nugraha, Achmad Tjachja; Amilia, Nurul; Megantari, Vetty (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: Cigarette filters are generally regarded as inert components composed primarily of cellulose acetate fibers and plasticizers such as triacetin. However, limited independent analytical studies have investigated the presence of additional compounds that may be incorporated during manufacturing. From a halal science perspective, the presence of proteinaceous materials or glycerol-related compounds may represent a potential halal critical point because their permissibility depends on their biological origin and processing method. This study conducted a preliminary screening of proteinaceous and glycerol-related compounds in several commercial cigarette filters using chromatographic and spectrometric analytical approaches. In addition, a hemoglobin-equivalent colorimetric assay was applied as an initial indicator of protein-like substances. The results indicated the presence of glycerol-related compounds consistent with commonly used plasticizers and humectants in cigarette filter manufacturing. The preliminary screening also suggested the presence of proteinaceous signals in certain samples, although the analytical approach used in this study does not allow for the confirmation of the species origin. These findings highlight the need for more comprehensive analytical verification, including advanced proteomic or DNA-based techniques, to determine the source of such compounds. The study underscores the importance of transparency in material sourcing and manufacturing processes for consumer products that may involve animal-derived substances. Furthermore, this research contributes to the development of analytical frameworks for identifying potential halal critical points in non-food consumer products such as tobacco-related materials. Abstrak: Filter rokok umumnya dianggap sebagai komponen inert yang terutama tersusun dari serat selulosa asetat dan plasticizer seperti triacetin. Namun demikian, kajian analitik independen yang meneliti keberadaan senyawa tambahan yang mungkin dimasukkan selama proses manufaktur masih sangat terbatas. Berdasarkan perspektif sains halal, keberadaan bahan bersifat protein (proteinaceous materials) atau senyawa yang berkaitan dengan gliserol berpotensi menjadi titik kritis halal, karena kehalalannya bergantung pada asal biologis serta metode pengolahannya. Penelitian ini melakukan skrining awal terhadap keberadaan senyawa proteinaceous dan senyawa terkait gliserol pada beberapa filter rokok komersial dengan menggunakan pendekatan analisis kromatografi dan spektrometri. Selain itu, uji kolorimetri hemoglobin-ekuivalen digunakan sebagai indikator awal untuk mendeteksi keberadaan zat yang menyerupai protein. Hasil penelitian menunjukkan adanya senyawa terkait gliserol yang konsisten dengan penggunaan plastisizer dan humektan yang umum digunakan dalam pembuatan filter rokok. Skrining awal juga menunjukkan adanya sinyal yang mengindikasikan keberadaan senyawa proteinaceous pada beberapa sampel, meskipun pendekatan analitik yang digunakan dalam penelitian ini belum memungkinkan konfirmasi asal spesiesnya. Temuan ini menegaskan perlunya verifikasi analitik yang lebih komprehensif, termasuk penggunaan teknik proteomik tingkat lanjut atau metode berbasis DNA, untuk menentukan sumber senyawa tersebut secara lebih pasti. Penelitian ini juga menekankan pentingnya transparansi dalam sumber bahan baku dan proses manufaktur pada produk konsumen yang berpotensi melibatkan bahan turunan hewani. Selain itu, penelitian ini berkontribusi dalam pengembangan kerangka analitik untuk mengidentifikasi potensi titik kritis halal pada produk konsumen nonpangan, seperti material yang berkaitan dengan produk tembakau.